Pengaruh Pemasaran Digital terhadap Penjualan pada Toko Pakaian Mega Mall Bengkulu - Ovita Charolina; Samsul Akmal; Desi Wulandari (Business Perspective Journal, 2023)
This study aims to determine the effect of digital marketing on sales at the clothing store Mega Mall Bengkulu. This type of research is quantitative, the sample in this study amounted to 55 clothing stores, the data collection method used was the distribution of questionnaires and the method of data analysis using SPSS. The results of the research on the validity test show that digital marketing is valid with a sig value. 2 tailed < 0.05 while in sales there is an invalid statement because it has a sig value. 2 tailed > 0.05. In the digital marketing reliability test, it is said to be reliable because X 0.984 > 0.60 while in sales it is said to be reliable because Y 0.511 > 0.60. In the normality test, digital marketing and sales have a normal distribution because it is significant with a value of 0.200 > 0.05. In the heteroscedasticity test there are no symptoms and in simple linear regression the constant value (a) is 26.842 or 2684% and the regression coefficient (b) x is 0.116 or 11.6% with a significant level of 0.000 it is said that digital marketing (X) has a positive effect on sales (Y). Keywords : Digital Marketing and Sales